The supramolecular modification of trans-resveratrol and related antioxidant molecules - Hunt, Lee Elizabeth (Department of Chemistry, 2017)
The naturally occurring phytoalexin trans-Resveratrol (RES) is known to be a powerful antioxidant and is used as a nutraceutical. It is considered to be one of the factors contributing to the beneficial effects of red wine. The phenolic hydroxycinnamic acids caffeic acid (CAF), ferulic acid (FA), p-coumaric acid (PCA) and sinapic acid (SA) are found in a wide variety of plants and also have antioxidant activity. The acetophenone derivatives paeonol (2H4M) and vanillin (4H3M) display antioxidant, anti-inflammatory and antihypertensive activity. The use of these compounds as food fortifiers and nutraceuticals is limited as they exhibit adverse physical properties such as low aqueous solubility and low bioavailability. These properties may be improved by inclusion complex formation with cyclodextrins (CDs) and by cocrystallisation with generally regarded as safe (GRAS) coformers. A study of the CD complexation of RES, CAF, FA, PCA, SA, 2H4M and 4H3M was carried out both in solution and in the solid state. The solubility enhancement of the nutraceuticals by CD inclusion and by cocrystallisation was evaluated. The compounds hydrocaffeic acid (HCA), hydroferulic acid (FA), 2-hydroxy-5-methoxy acetophenone (2H5M) and 2-hydroxy-6-methoxy acetophenone (2H6M) have little or no known bioactivity but were included in the study as structural analogues for comparative purposes. Inclusion complexes were formed with the nutraceuticals and the native CDs (β- and γ-CD) by kneading and coprecipitation, as well as with methylated CDs by coprecipitation. The resulting inclusion complexes were characterised using powder X-ray diffraction (PXRD), ¹H nuclear magnetic resonance spectroscopy (¹H-NMR), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) and hot stage microscopy (HSM). Single crystal X-ray diffraction was used to elucidate inclusion complex structures. Three novel RES inclusion complexes were formed with methylated CDs having common modes of inclusion and hydrogen bonding motifs. Inclusion complex formation with the methylated CDs also produced six new hydroxycinnamic acid complexes and five new hydroxyacetophenone complexes. While attempting to produce native CD inclusion complexes with the hydroxycinnamic acid compounds, crystals of SA were isolated, the structure of which had not been reported previously. The results of phase solubility studies revealed that, in general, CD inclusion complex formation improves the aqueous solubility of RES [randomly methylated CD (RAMEB) effecting a maximum increase of 63 times that of free RES] and hydroxycinnamic acids. The thermodynamic parameters and association constants for complexation between hydroxycinnamic acids and both β- and γ-CD were determined by isothermal titration calorimetry (ITC). For β-CD a 1:1 host-guest ratio was found with association constants in the range 246-774 M⁻¹. The interactions between the guests and β-CD were found to be enthalpy-driven, except for that of SA and β-CD which was entropy-driven. With γ-CD a 1:1 host to CAF ratio was found while PCA, FA and SA interact with γ-CD in a 2:1 molar ratio. The association constants were in the range 228-543 M⁻¹. The formation of 2:1 complexes in solution was found to be enthalpy-driven while that of 1:1 complexes was entropydriven. ¹H NMR spectroscopy was used to study the interaction of the acetophenone derivatives with β- and γ-CD in solution. Job plot analyses confirmed 1:1 host-guest complex ratios. The association constants spanned the range 145-336 M⁻¹. Similarly for γ-CD, complex stoichiometries were confirmed to be 1:1 with 2H6M and 4H3M with association constants 67 and 125 M⁻¹, respectively. Eight cocrystals were prepared with hydroxycinnamic acids and the GRAS compounds nicotinamide (NIC) and isonicotinamide (ISO) by coprecipitation, and were fully characterised. Single crystal X-ray diffraction confirmed the formation of cocrystals rather than salts. Analysis using ¹H NMR spectroscopy for quantitation revealed that the aqueous solubilities of FA and PCA were enhanced approximately ten-fold when tested in the form of their cocrystals with the coformer NIC.